Comparison of Functional Outcome after Extended versus Super-Extended Pelvic Lymph Node Dissection during Radical Prostatectomy in High-Risk Localized Prostate Cancer - Seikkula, Heikki; Janssen, Pieter; Tutolo, Manuela; Tosco, Lorenzo; Battaglia, Antonino; Moris, Lisa; Van den Broeck, Thomas; Albersen, Maarten; De Meerleer, Gert; Van Poppel, Hendrik; Everaerts, Wouter; Joniau, Steven (Frontiers in Oncology, 2017)
Background: Urinary continence and erectile function (EF) are best preserved when meticulous dissection of prostate and nerve-sparing technique are used during radical prostatectomy (RP). However, extent of lymph node dissection (LND) may also adversely affect functional results. Objective: To determine whether performing a super-extended LND (seLND) has a significant effect on recovery of urinary continence and EF after RP. Design, setting, and participants: All patients who underwent RP from January 2007 until December 2013 were handed questionnaires assessing continence and EF. All patients in whom at least an extended LND (eLND) was performed were selected. This search yielded 526 patients. 172 of these patients had filed out 2 or more questionnaires and were included in our analysis. Outcome measurements and statistical analysis: All questionnaires were reviewed. We used Kaplan-Meier analyses and multivariate Cox analysis to assess the difference in recovery of continence and EF over time for eLND/seLND. Primary endpoints were full recovery of continence (no loss of urine) and full recovery of EF (successful intercourse possible). Patients who did not reach the endpoint when the last questionnaire was filled out were censored at that time. Median follow-up was 12.43 months for continence, and 18.97 months for EF. Results and limitations: Patients undergoing seLND have a lower chance of regaining both urinary continence (Hazard ratio(HR) 0.59, 95% CI 0.39-0.90, p=0.026) and EF (HR 0.28, 95%CI 0.13-0.57, p=0.009). Age at surgery had a significant influence on both continence and EF in multivariate analysis. Major limitation of the study was that no formal preoperative assessment of continence and potency was done. Conclusions: Extending the LND template beyond the eLND template may cause at least a significant delay in recovery of urinary continence and leads to less recovery of EF.